PENGEMBANGAN GAME 2D PLATFORMER “VIRUS MUST DIE” BERBASIS ANDROID MENGGUNAKAN UNITY - Prayoga, Dimas; Lili Rusdiana; Fenroy Yedithia (STMIK Palangkaraya, 2022)
The development of an Android-based 2d platformer game with elements of Artificial Intelligence (AI) on certain objects makes users get entertainment. However, with the addition of educational elements simultaneously when playing games, it will directly increase user knowledge. The purpose of this study is to present games in the form of education about mathematics to users. The methods used include literature study, observation, and experiment. The software development method uses the System Development Life Cycle (SDLC) with a waterfall development approach. The software used in making this game is unity version 2020.3.1f1 Long Term Support (LTS). Testing using black box testing with good results. Based on the results of the questionnaire, this game is said to be suitable for use with a percentage value of 82.4%.